Implementation of marketing strategy 4.0 to pastry producers in Taman District, Sidoarjo Regency - Indah Sulistiyowati; Ali Akbar; Fitri Nur Latifah (Universitas Muhammadiyah Magelang, 2021)
The COVID-19 pandemic has caused Danish Cake SMEs to experience a decline in turnover of up to 30%. This is due to the focus on offline product marketing, both through agents and resellers. While the pandemic has changed the way of shopping, most consumers prefer online shopping, because it is considered safer and minimizes direct contact with sellers. The problem-solving method used is to optimalize the marketing 4.0 strategy that combines offline and online interactions between producers and customers. For online channels, the service team created a shopping application via an Android phone as a virtual shopping facility and created a paspastry.com website which also functions as a customer database. With this application, consumers just shop through their respective cellphones, choose the desired cake, make a payment, and the cake will be sent to the buyer's house. Another use of online channels is to improve promotional content through Instagram, Facebook, and fanpages as well as by creating accounts on marketplaces such as Shopee. With the implementation of the Marketing 4.0 strategy, Danish Cake SMEs will increase their product sales, both online and offline, in addition to increasing branding awareness of the product.